Wakaf Zurri: Instrumen Pengurusan Harta dalam Pembangunan Tamadun Islam: Waqf Zurri: An Instrument for Estate Planning in Developing Islamic Civilization - Ahmad Sanusi, Sri Wahyu Sakina; Yaacob, Salmy Edawati; Md Salleh, Mohd Fairuz (Journal of Al-Tamaddun, 2021)
Zurri waqf stands as an alternative for estate planning upon the death of one’s parents. Despite having current alternative such as will writing, faraid and hibah, zurri waqf is viable as instrument to distribute wealth to the loved ones. Data given by Jabatan Ketua Pengarah Tanah dan Galian (JKPTG) in 2019 shows a total of RM60 billion of unclaimed property had been recorded. Amongst of the causes are; absence of will writing and little knowledge of wealth management from the heirs. Thus, zurri waqf stand as one mechanism which can be practiced to assist the parentless child in surviving their lifes. Therefore, the objective of this study is to identify the zurri waqf instrument as an estate planning and to identify the zurri waqf management procedures in Malaysia. This study is a qualitative nature in the form of interview and content analysis. This paper benefits readers and researchers involved in gaining more knowledge about zurri waqf as a suitable instrument for the estate planning of Muslim property such as land cultivated as agriculture and involving the participation of beneficiaries in waqf assets development that can bring significant impact in the future. In addition, the zurri waqf management procedures need to be improved in order to encourage its implementation in the future.